G197(P) Overcoming the challenges of managing HIV exposed infants in a District General Hospital. (7th April 2014) - Norrish, G; Wedderburn, C; Wickham, T; Shah, R
Abstract : Aims: The majority of children living with HIV acquired their infections via mother to child transmission (MTCT). The risk of MTCT can be significantly reduced with anti-retroviral medication, appropriate delivery method and avoidance of breast feeding, as detailed in the 2012 BHIVA guidelines for the 'management of pregnant women with HIV'. An audit was undertaken to look at how successfully the national guideline were implemented in a district general hospital (DGH). Methods: Data from the records of all neonates born to HIV infected mothers at a district general hospital between 2008–2012 was collected including maternal, birth and postnatal care. Targets of 100% were set for each data standard comparing to the 2012 BHIVA guidelines. Results: 33 infants were identified. 50% of the mothers were new HIV diagnoses in this pregnancy. 100% of the mothers were on Highly Active Anti-retroviral Treatment (HAART). 27 babies were low risk for transmission and all were started on appropriate post-exposure prophylaxis (PEP). 6 infants were high risk for transmission, with an unsuppressed maternal viral load at delivery – 5 were started on appropriate PEP therapy however 1 patient was inappropriately started on AZT monotherapy. Prescribing mistakes were made in 3 patients. PEP was given within 4 h in 95% of patients. 3 patients were lost to follow up at 18 months. All other patients were seen in the out-patient setting although appointment timing varied from guidelines. There was 1 confirmed vertical transmission of HIV in which maternal non-adherence was a significant concern. Conclusions: DGH's are responsible for the care of a significant number of HIV exposed infants. National guidelines describe gold standard treatment and as such need to be adopted within district general hospitals, which may have less specialised health care professionals. Junior members of staff are often responsible for the day-to-day management of these infants but often lack experience and rotate regularly through clinical placements during training. This can lead to errors which impact negatively on patient care. To counteract this problem, and facilitate multidisciplinary working, a clear, user-friendly proforma has been developed which we recommend could be used widely in the DGH setting.